The Impact of The COVID Pandemic on The Lending of Banks Operating in Poland - Małgorzata Białas; Izabela Emerling (Communications of International Proceedings, 2021)
In recent years, characterized by the dynamic development of capital and money markets and economies of many countries, the demand for complete, up-to-date and reliable information on the property and financial situation as well as on the financial results of enterprises and clients applying for financing in financial institutions conducting banking activity has increased. The pandemic had a major impact on the economic and financial situation of business entities and customers. In the era of COVID 19, many entities had to temporarily suspend their activities, which contributed to the search for sources of financing in the form of bank loans. The aim of the article is to analyze whether the pandemic has affected the quantity and quality of loans granted by banks. The main research objective of the article is to examine and compare the number and types of loans granted in Poland in the years preceding the crisis caused by COVID 19 the pandemic and in 2020 during this pandemic, as well as to assess the impact of the pandemic on the volume of lending to enterprises and bank customers. The basic research hypothesis is: The COVID 19 crisis contributed to the deterioration of the quality and quantity of loans granted by banks in Poland. The verification of the above research hypothesis is the main goal of this article. The applied research methods are based on literature studies in the studied area and the analysis of numerical data concerning loans valued at amortized cost for the bank's clients, such as enterprises. The analysis was carried out on the basis of financial data contained in quarterly reports of selected banks in Poland in 2018-2021 and information on the condition of the banking sector in Poland published by the Polish Financial Supervision Authority.